Cogumelos do gênero "Psilocybe" nas Américas e no Brasil: Sua história com a humanidade, seus diversos usos e sua cosmopolítica - Lino, Anita (Anthropology of consciousness, 2026)
This paper examines the intimate relationship of affection, consumption, and ritual practice between humanity and mushrooms of the genus Psilocybe, focusing mainly on the Americas and Brazil. To this end, it uses reflections that present the American continent as a macroregion historically marked by transits, connections, and exchanges since pre-Columbian times, and where there is significant access and also endemicity of the aforementioned fungal species with which human beings have carried out and carry out practices of mycophagy, mycophilia, and/or mycolatry. Bringing information that allows us to understand the historical importance of the psilocybe mushroom in the cultures of this continent and its growing presence in relations with humanity in Brazil, this article proposes to broaden the lens in a perspective that considers ritual, oracular, therapeutic, philosophical, scientific, aesthetic, and recreational experiences as ways of ritualizing and expressing affection with this species of the Fungi Kingdom, many of them inspired by Amerindian practices. Thus, this article considers and reflects on the importance of psilocybin culture in Brazil, concluding with observations regarding the cosmopolitical implications of the use of these mushrooms for various purposes in the country.